2018
DOI: 10.1016/j.jcin.2018.03.046
|View full text |Cite
|
Sign up to set email alerts
|

1-Year All-Comers Analysis of the Eluvia Drug-Eluting Stent for Long Femoropopliteal Lesions After Suboptimal Angioplasty

Abstract: The fluoropolymer-based PES showed promising 1-year clinical and angiographic outcomes in real-world long femoropopliteal lesions. The long-term impact of aneurysm formation remains to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 28 publications
1
58
2
1
Order By: Relevance
“…However, these studies provide a range of reference and context for the IMPERIAL study results. In a registry of Eluvia use at a single European center, a 12-month primary patency rate of 87% in patients with a mean lesion length of 20 cm (48% with CLTI) was reported, 13 further supporting the notion of independence between patency and lesion length for patients treated with Eluvia. Treatment of long lesions with the paclitaxelcoated Zilver PTX stent yielded 1-year primary patency rates of 52.5% in a single-center registry in France (mean lesion length 25 cm, 51% with CLTI at baseline) 14 and 86.4% in a multicenter registry in Japan (mean lesion length 14.7 cm, 21.5% with CLTI).…”
Section: Discussionmentioning
confidence: 69%
“…However, these studies provide a range of reference and context for the IMPERIAL study results. In a registry of Eluvia use at a single European center, a 12-month primary patency rate of 87% in patients with a mean lesion length of 20 cm (48% with CLTI) was reported, 13 further supporting the notion of independence between patency and lesion length for patients treated with Eluvia. Treatment of long lesions with the paclitaxelcoated Zilver PTX stent yielded 1-year primary patency rates of 52.5% in a single-center registry in France (mean lesion length 25 cm, 51% with CLTI at baseline) 14 and 86.4% in a multicenter registry in Japan (mean lesion length 14.7 cm, 21.5% with CLTI).…”
Section: Discussionmentioning
confidence: 69%
“…The causes of vessel injury included oversized balloons, high-pressure inflation, stent fracture, or infection [13]. Although the precise pathophysiology is unknown, paclitaxel may be implicated due to a combination of cytotoxic effects on the vascular wall, hypersensitivity-related extensive inflammation, and delayed neointimal healing [6,[16][17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, negative LLL was observed in 23% patients (8 of 35) of the Eluvia group, wherein the vessel diameter during the chronic phase was larger than that at the final imaging. To investigate previously reported information on aneurysmal degeneration 15) , we performed duplex ultrasound for all cases, but aneurysmal degeneration was not observed in the present study. Similarly, for angiographic follow-up, there was no aneurysmal change exceeding the stent diameter.…”
Section: Baselinementioning
confidence: 95%